Metagenomic insights into particles and their associated microbiota in a coastal margin ecosystem - Simon, Holly M.; Smith, Maria W.; Herfort, Lydie (Frontiers in Microbiology, 2014)
Our previously published research was one of the pioneering studies on the use of metagenomics to directly compare taxonomic and metabolic properties of aquatic microorganisms from different filter size-fractions. We compared size-fractionated water samples representing free-living and particle-attached communities from four diverse habitats in the Columbia River coastal margin, analyzing 12 metagenomes consisting of >5 million sequence reads (>1.6 Gbp). With predicted peptide and rRNA data we evaluated eukaryotic, bacterial and archaeal populations across size fractions and related their properties to attached and free-living lifestyles, and their potential roles in carbon and nutrient cycling. In this focused review, we expand our discussion on the use of high-throughput sequence data to relate microbial community structure and function to the origin, fate and transport of particulate organic matter in coastal margins. We additionally discuss the potential impact of the priming effect on organic matter cycling at the land-ocean interface, and build a case for the importance, in particle-rich estuaries and coastal margin waters, of bacterial activities in low-oxygen microzones within particle interiors.